OPTIMIZATION AND CHARACTERIZATION OF PECTINASE PRODUCED BY ASPERGILLUS FLAVUS SS13 USING CITRUS PEEL - Ja'afaru, Mohammed I.; Ogwuche, Justice O.; Adeyemo , Olumuyiwa M.; Bernard, Adati L. (FUDMA JOURNAL OF SCIENCES, 2025)
Pectinases have multipurpose applications in both industrial and biotechnological sectors. But they are expensive when available. This study was carried out to isolate fungi, screen them for pectinase activity, identify selected fungi isolate, mutate, optimize, produce, and characterize the partially purified pectinase. Aspergillus flavus SS13 was isolated using standard technique, it exhibited the highest pectinase activity of 36.0±0.3 mm zone of hydrolysis and it was identified based on its macroscopic and microscopic characteristics. EMS mutated A. flavus SS13 had a pectinase activity of 40±0.2 U/mL, UV-mutated A. flavus SS13 exhibited 36.0±0.5 U/mL while the SA-mutated A. flavus SS13 showed pectinase activitiy of 35±0.4 U/mL, and unmutated A flavus SS13 had 28.0 ±0.2 U/mL at pH 3.0, temperature 40 °C and incubation period of 96 h utilizing orange peel as carbon. The partially purified pectinase of A. flavus SS13, A. flavus SS13-EMS, A. flavus SS13-UV, and A. flavus SS13-SA had between 1.3 to 1.5 fold purification and 26.0 to 30.0 % recovery. The partially purified pectinase of A. flavus SS13 wild type and the three mutants had improved activity in the presence of tween-80, while a significant pectinase activity was noted with cations such as Cu2+, Ca2+, and K+ in all the three mutants’ enzyme while the ions of ammonium, cobalt, and sodium repressed pectinase activity in the wild type A. flavus SS13. The stability of the pectinase produced by the mutants at acidic pH and elevated temperature could be an added advantage for its diverse applications in the food, detergent,...